PERANCANGAN KAPAL KONTAINER 220 TEUS KECEPATAN 12 KNOT UNTUK RUTE TANJUNG PRIOK - BELAWAN - Ressica Ayu Elhas, (2020)
CONTAINER SHIP DESIGN 220 TEU SPEED 12 KNOTS FOR TANJUNG PRIOK-BELAWAN ROUTE DELIVERY Ressica Ayu Elhas ABSTRACT Container ships are ships specifically used to carry containers. Medan has an International Container port, so with the rise of the modern coffee business, Medan can become a center for export of coffee and spices in North Sumatra and its surroundings to Jakarta. And Medan also needs staples and food that can be imported from Jakarta (Tanjung Priok Port). In this thesis the author takes the theme of Designing 220 Teus Container Ships as a means of transporting coffee and spices typical of the terrain and staples from the Port of Tanjung Priok-Belawan. The author gets the main data of the ship by using a comparative ship. The main measurements obtained from the calculations in this design are LOA: 103.97 m, LWL: 101.92 m, LPP: 98 m, B: 17, H: 10.3 m, T: 7.1 m, CB: 0.778, Displacement: 9434,653 tons, Vs: 12 knots. This ship uses a 4000 kW main engine and a propeller with 5 leaves. The division of the crew consists of 38 people with safety equipment that follows applicable standards. Construction uses BKI rules for container ships. Floodable Length uses the Webster table method. The ship's strength contains sagging, hogging and buckling. The rolling period of the ship is in the 8-14s. Launch using the elongated launch method. Keywords: Container ships, one comparison, cargo, route, coffee and chocolate, design